The German health care system in international comparison: the primary care physicians’ perspective - Koch, Klaus; Miksch, Antje; Schürmann, Christoph; Joos, Stefanie; Sawicki, Peter (Deutsches Ärzteblatt, 2011)
Background: In 2009, the U.S. Commonwealth Fund conducted a survey of primary care physicians in a number of different countries to determine their views on aspects of their daily work and their perceptions of their countries’ health care systems as a whole. A similar survey had been carried out in 2006. Methods: From February to July 2009, the survey was carried out by interview in representative samples of primary care physicians, general practitioners, internists providing primary care, and pediatricians in 11 countries: Australia, Canada, France, Germany, Italy, the Netherlands, New Zealand, Norway, Sweden, the UK, and the USA. Results: A total of 10 320 interviews were conducted. Only in the Netherlands and Norway did most respondents (60% and 56%, respectively) consider their health care system to be functioning well. Everywhere else, many of the respondents—in particular, 82% of the respondents in Germany—saw a fundamental need for change. 73% of the German physicians stated that recent changes in the health care system had brought about a decline in the quality of care. In all countries but Germany, the percentage of respondents sharing this opinion was 41% at the highest. Nevertheless, most of the German physicians had a positive opinion of the patient care that they themselves delivered. Conclusion: The 2009 survey, like its predecessor in 2006, revealed major differences in physicians’ perceptions of their health care systems from one country to another. The German respondents’ dissatisfaction with, and negative evaluation of, their health care system as a whole contrast with their positive views of their own patient care.
Gesehen am 19.08.2022